Gambaran Intensi Guru dalam Menerapkan Pendidikan Seksualitas pada Siswa Kelas IV-VI SD N di Jakarta - Sylvia Febrianti; Margaretha Purwanti (Fakultas Psikologi Universitas Tarumanagara, 2018)
The exposure to matters related to sexuality and pornography makes sexuality education for elementary students an important thing to do. The goals are to equip and empower young people with the information, skills and positive values, and to make young people understand and responsible for their sexuality health and wellbeing. Cases relating to the issue of sexuality have begun to appear in students of grade 4-6 at SD N, but teachers appear not to have fully applied sexuality education to their students. This study aims to get an idea about teacher’s intention, included teacher’s attitude toward behavior, subjective norm, and perceived behavior control in teaching sexuality to grade 4-6 students. The research design used in this study is mixed-method design. The number of participants of this study are 20 people (50% male and 50% female) with age range from 24 years old to 42 years old. The results showed that the majority of teachers (55%) have moderate intention, high attitude toward behavior (80%), moderate subjective norm (80%) and moderate perceived behavior control (65%). The results also showed that only perceived behavior control has a significant relationship with the intention (r= .617, p<0.05).